2018
DOI: 10.1016/j.imr.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Pinpoint Plantar Long-Wavelength Infrared Light Irradiation (Stress-Free Therapy) on Chorioretinal Hemodynamics, Atherosclerosis Factors, and Vascular Endothelial Growth Factor

Abstract: BackgroundWe previously reported that pinpoint plantar long-wavelength infrared light irradiation (stress-free therapy; SFT) is useful for alleviating insulin resistance and improving intracranial blood flow in patients with type 2 diabetes mellitus. This study was undertaken to evaluate the influences of SFT on chorioretinal hemodynamics (retinal artery and vein blood flows) as well as atherosclerosis-related factors (TG, LDL-C) and VEGF in patients with dyslipidemia.MethodsFour patients with dyslipidemia rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The relationship between chronic stress and intimal (and media) thickness was not clear in previous scholarship [ 14 , 15 ]. ZM Yu and her colleagues [ 11 ] found that chronic stress may promote the apoptosis of smooth muscle cells and lead to thinner media thickness in the blood vessels.…”
Section: Discussionmentioning
confidence: 95%
“…The relationship between chronic stress and intimal (and media) thickness was not clear in previous scholarship [ 14 , 15 ]. ZM Yu and her colleagues [ 11 ] found that chronic stress may promote the apoptosis of smooth muscle cells and lead to thinner media thickness in the blood vessels.…”
Section: Discussionmentioning
confidence: 95%
“…Among them, the wavelength range of far-infrared rays (FIRs) as defined in the medical field is 5.6-1000 µm [1]. As the energy of far-infrared rays can promote blood circulation [2][3][4], cell repair [5], tissue regeneration [3,6], intestinal function [7], diminish inflammation [8], and inhibit cancer [9], it is often used in medical, health, and beauty fields [10]. However, the action mechanisms of FIR on humans are still little known [10].…”
Section: Introductionmentioning
confidence: 99%